Ecological predictions - Law, Andrew (Milton Keynes : Open University Worldwide)
Focuses on works at little weapon homenature to look at 3 problems in ecology that can be done by using statistical simulation
Keywords: Ecology -- Simulation methods; Ecology -- Research